O legado do sistema colonial na América Latina - Sara Almarza (Caravelle)
Based upon Brazilian, Mexican and Peruvian documents, this article illustrates how, through the language, the uneasiness of colonial life revealed itself and how the fundamental terms of historical and sociological vocabulary –fatherland, America– were employed with a different meaning ; that’s how countries’ identity first started to express itself. This study favours the first rebellions and the arrival of new mentalities. At the same time, it revisits the ideas of a few Latin Americans intellectuals belonging to the independence century and tries to display some characteristics of contemporary Latin America’s reality.